1993
DOI: 10.1017/s0025315400033117
|View full text |Cite
|
Sign up to set email alerts
|

Food of striped dolphin, Stenella coeruleoalba, in the Ligurian Sea

Abstract: The stomachsof 23 striped dolphins (Stenella coeruleoalba Meyen, 1833, Cetacea), stranded along the Ligurian coast (western Mediterranean Sea), contained 32 species of cephalopods, crustaceans and fishes, totalling an estimated 2,723 prey specimens representing about 36 kg in weight. Cephalopods and bony fishes were equally important in the diet (50%).Todarodes sagittatus (34-5%) and Micromesistius poutassou (25-9%) were found to be the most important food species . Other species belonging to six cephalopod fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
2
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 3 publications
7
42
2
1
Order By: Relevance
“…In comparison with other species analyzed by Capelli et al (2008), toothed whales seem to present trophic levels superior to the two fin whales Balaenoptera physalus (d 15 N = 8.3‰ and 9.3‰) and the three striped dolphins Stenella coeruleoalba (d 15 N from 8.9‰ to 9.5‰), similar to one Cuvier's beaked whale (d 15 N = 10.6‰) and inferior to two bottlenose dolphins Tursiops truncatus (d 15 N = 12.6 and 13.5‰). Such results are in accordance with previous stomach content analyses (Blanco and Raga, 2000;Orsi Relini and Giordano, 1992;Würtz and Marrale, 1993). In the Strait of Gibraltar (connecting the Mediterranean Sea and the Atlantic Ocean), pilot whales showed higher d 15 N and d…”
supporting
confidence: 92%
“…In comparison with other species analyzed by Capelli et al (2008), toothed whales seem to present trophic levels superior to the two fin whales Balaenoptera physalus (d 15 N = 8.3‰ and 9.3‰) and the three striped dolphins Stenella coeruleoalba (d 15 N from 8.9‰ to 9.5‰), similar to one Cuvier's beaked whale (d 15 N = 10.6‰) and inferior to two bottlenose dolphins Tursiops truncatus (d 15 N = 12.6 and 13.5‰). Such results are in accordance with previous stomach content analyses (Blanco and Raga, 2000;Orsi Relini and Giordano, 1992;Würtz and Marrale, 1993). In the Strait of Gibraltar (connecting the Mediterranean Sea and the Atlantic Ocean), pilot whales showed higher d 15 N and d…”
supporting
confidence: 92%
“…Those optimum conditions were met in the Tyrrhenian Sea, along the lower slope of the western Sardinia/Corsica margin and the south Balearic Islands. These areas of high density were consistent with the habitats of the known forage species, such as blue whiting Micromesistius poutassou for example [31].…”
Section: Ecological Preferencessupporting
confidence: 78%
“…However, the common dolphin samples included all the ®sh species found in the diet of the albacore whereas only one species of prey was found in both striped dolphin and tuna stomachs. Each species seems to have preferential preys but it has been demonstrated that striped and common dolphins are quite opportunistic feeders and can take advantage of seasonally or locally abundant preys (Wurtz and Marrale, 1993;Blanco et al, 1995;Young and Cockroft, 1995). For example, in the Northwest Atlantic, the diet of common dolphins consists mainly of longer sized ®sh as capelins (Mallotus villosus) and mackerels (Scomber scombrus) (Overholtz and Waring, 1991;Ostrom et al, 1993).…”
Section: Discussionmentioning
confidence: 99%